Characteristic Analysis of Type 2 Diabetes Mellitus Based on HbA1C - Andarmoyo, Sulistyo; Yusoff, Harmy Mohamed; Abdullah, Berhanudin; Yusop, Yuzana Mohd (Jurnal Keperawatan, 2020)
Introduction: Type 2 Diabetes Mellitus (DM) is a group of metabolic diseases with hyperglycemia characteristic that occurs due to insulin resistance accompanied by relative insulin deficiency. Monitoring the metabolic status of DM patients is important. One method that can be used to determine blood glucose control in people with DM is measurement of hemoglobin-glycosylated (HbA1c). Objective: The purpose of this study is to determine the characteristics of DM patients based on HbA1c levels in Ponorogo Regency, East Java, Indonesia. Method: The study used a cross-sectional design, and descriptive data presentation. The study took a sample of 180 people with type 2 diabetes in Ponorogo Regency. Respondent characteristic data in the form of age, sex, education and duration of DM were obtained through interviews, and HbA1c values were obtained by blood tests in a standardized laboratory in Ponorogo Regency. Results: The results of the study shows that 81.7% of 180 DM patients had 16.5% HbA1c values. Patients with HbA1c â‰¥6.5% are mostly women, old age, low education, and have had suffered DM less than 5 years. Discussion: To prevent further complications, glycemic control is needed through routine and periodic HbA1c checks.